Islamicity Performance Index, Good Corporate Governance Quality dan Kinerja Keuangan Bank Umum Syariah di Indonesia - Maisaroh, Siti; Pratama, Versiandika Yudha (Department of Islamic Banking, 2023)
This research aims to know the impact of Islamicity Performance Index and the quality of Good Corporate Governance on the financial performance of the Sharia Bank. This research includes correlation studies with quantitative methods. The type of data used in this study is secondary data obtained from financial statements, GCG reports and annual reports. The sampling technique used was a side purposive technique so that 7 Islamic Commercial Banks were obtained as samples. The data analysis technique uses multiple linear regression with the F test and t test. The results of the study showed that Profit Sharing Ratio, Equitable Distribution Ratio and the Board of Directors had a significant impact on the ROA of Sharia Bank Indonesia in the 2017-2021 period. While the Zakat Performance Ratio variable, the Sharia Supervisory Board and the Audit Committee have no significant influence on the ROA of Sharia Bank Indonesia for the period 2017-2021. This research has the implication that by using the Islamicity Performance Index and Good Corporate Governance approaches used in analyzing social performance and governance, it can be used to measure performance of Islamic Commercial Banks by looking at the weaknesses and strengths so that evaluations can be carried out more effectively.